Dampak Literasi Keuangan terhadap Kinerja Keuangan pada Usaha Mikro Kecil dan Menengah di Samarinda - M. Astri Yulidar Abbas; Sri Wahyuti; Sugiarto, Sugiarto; Ni Putu Sinta Ayu; Syafrullah, Syafrullah (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2024)
The purpose of this group community service is to increase understanding of the importance of financial literacy on the financial performance of Micro, Small and Medium Enterprises in Samarinda. A lack of understanding in financial literacy has an impact on the limited ability of Micro, Small and Medium Enterprises to utilize existing financial products and services. The method used in the service is lectures and discussions with participants which are carried out in four stages consisting of identification, training in preparing financial reports, socialization on how to apply for loans, and evaluation. The results of the activity showed that before the socialization on financial literacy was held, only 35% of participants understood about financial products and services while understanding the importance of financial management, only 50% of the total participants. After the socialization, 85% of participants understood the importance of financial literacy and financial management to improve their financial performance and utilizing financial products and services optimally to increase their funding and financial performance. To further optimize this activity, continuous training and mentoring is needed in the form of coaching and training in the technical process of recording and making financial reports on Micro, Small and Medium Enterprises